Konsep Kewalian Menurut Syeikh Abdul Qodir Al-jailani - Mahya, Mimi Jamilah (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2021)
In tasawwuf, sainthood is one of the most important topics, which sheikh ‘Abd Al-Qodir Al-Jailânî even considers indispensable to the term tasawwuf itself. Indonesian Muslims ascribe sainthood to those honourable religious figures of high rank and reputation. This article expounds the concept of sainthood according to sheikh ‘Abd Al-Qodir Al-Jailânî with special reference to his three books, Sir Al-Asrâr, Al-Fath Al-Robbanî and Futûh Al-Ghoib. The discussion includes conceptual definition, methods to reach sainthood rank/level, the saints’ characteristics, infallibility and knowledge of their own sainthood and others’ sainthood as well as their karômah.